Problematika Pembelajaran Bahasa Arab bagi Mahasiswa Nonmadrasah: Suatu Kajian Analysis Solving - Ridwan (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aims to explore the problems faced by non-madrasah students In learning Arabic using a literature review method. Extensively, the existence of Arabic in the world of education is very significant with its recognition as an international language by the United Nations (UN). However, the learning experience of non-madrasah students is crucial. The results of this study indicate that the problems faced by students are linguistic barriers, psychological factors, and social aspects that influence their learning process. Linguistic barriers include difficulties in language rules and vocabulary. Psychological factors include anxiety and lack of self-confidence, and social aspects include social isolation and community support play a significant role in their learning experience. This study recommends the development of relevant and varied learning materials, the implementation of interactive teaching methods, and ongoing psychological support. These findings are expected to make a significant contribution to the development of Arabic curriculum and teaching practices that are more inclusive and responsive to the learning needs of non-madrasah students.